Avaliação nutricional de silagens de quatro genótipos de girassol (Helianthus annuus) - Diogo Gonzaga Jayme (2007)
The objective of this work was to study the nutritional value of the ensilages of four genotypes of sunflower, by determination of its chemicals compositions and studies of voluntary intake and apparent digestibility, in situ degradability and semi-automated in vitro gas production technique. The texts of dry matter (DM) of the genotypes used in this experiment had been satisfactory. The concentrations of crude protein (CP) of the used ensilages had varied of 6.75% for Victoria 627 7.83% for Mycogen 93338. The ensilages of the present experiment hadpresented average of 48.43% of neuter detergent fiber NDF. Already the values of acid detergent fiber (ADF) had varied of 24.04 32.29%. The values of EE of the ensilages that had been offered to the animals in this experiment had varied of 10.68% for Rumbosol 91 17.21% for Victoria 807. How much to gross energy (GE) texts the observed variation was of 4.26 the 4.63 Mcal/kg for the ensilages of the genotypes 91 Rumbosol and Victoria 807 respectively. Dry matter intake in grams per metabolic weight (g/MW) ranged from 59.9 (Mycogen 93338) to 85.0 g/MW/day (Victoria 627). Dry matter apparent digestibilities values were: 48.69% toRumbosol 91 genotype silage, 49.52% to Victoria 807 silage, 50.70% to Mycogen 93338 silage and 57.42% to Victoria 627, with no differences (p>0.05) between genotypes. The gross energy silages intake ranged from 252.0 g/MW/day to Rumbosol 91 genotype silage to 402.0g/MW/day to Victoria 627 silage. Values of gross energy apparent digestibilities ranged from 44.9% to Rumbosol silage to 55.58% to Victoria 627 silage. However highest values of digestible energy intake and metabolizable energy intake were observed to Victoria 627genotype silage. The crude protein intake varied from 5.39 g/MW/day to Rumbosol 91 genotype silage to 7,47 g/MW/day to Victoria 627 silage. No differences (p>0.05) were found to parameters of NDF intake and digestibility. Highest (p<0.05) ADF apparent digestibilities values were Victoria 627 with 39.84% and Mycogen 93338 with 42.67%. The lowest (p<0.05) ADF intake value obtained was Rumbosol 91 with 12.62 g/MW/day. Highest values of disappearance of the DM in times of 72 and 96 hours of incubation had been observed for the genotype Rumbosol 91 with values of 68.16% and 68.61% respectively. Highest values ofdisappearance of the DM in times of 72 and 96 hours of incubation had been observed for the genotype Rumbosol 91 with values of 68.16% and 68.61% respectively. Rumbosol 91 genotype presented highest PCG for time of 96 hours of incubation with value of 128.47 mL/g of DM. Nodifferences between values of DMD for silages evaluated in the different times were observed. Highest production of gases occurred on of six hours of fermentation, probably by readily available carbohydrates fermentation. This way, it can be suggested that Rumbosol 91 silagepossess greater concentration of soluble carbohydrates. Maximum potentials gas production ranged from 88.23 for Victoria 807 to 120.25 mL/g of DM Rumbosol 91, demonstrating that this material highest ruminal degradation. Genotype Rumbosol 91 presented biggest DMD forthe fermentation rate of 2 and 5% with values of 36.80 and 26.91%. Biggest value for rate of 8% was observed for Victoria 627 genotype. The data gotten in this work allow to indicate the sunflower as an option for use in the form of ensilage at the time of double-cropped.